Profound anterograde amnesia following routine anesthetic and dental procedure: a new classification of amnesia characterized by intermediate-to-late-stage consolidation failure?. Issue 1 (2nd January 2016) - Burgess, Gerald H.; Chadalavada, Bhanu
Abstract : Anterograde amnesia caused by bilateral hippocampal or diencephalon damage manifests in characteristic symptoms of preserved intellect and implicit learning, and short span of awareness with complete and rapid forgetting of episodic material. A new case, WO, 38-year-old male with anterograde amnesia, in the absence of structural brain changes or psychological explanation is presented, along with four comparison cases from the extant literature that share commonalities between them including preserved intellect, span of awareness greater than working memory, and complete forgetting within hours or days following successful learning, including notably for both explicit and implicit material. WO's amnesia onset coincided with anesthetic injection and root canal procedure, with extended vasovagal-like incident. The commonalities between the five cases presented may suggest a shared biological mechanism involving the breakdown of intermediate-to-late-stage consolidation that does not depend on the structural integrity of the hippocampi. Speculation on the mechanism of consolidation breakdown and diagnostic implications are discussed.